ANALISIS POLA PERSEBARAN PENYAKIT LEPTOSPIROSIS DI KOTA SEMARANG TAHUN 2014 – 2016 - Lirih Setyorini; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
Leptospirosis is carried by a pathogenic species of the genus Leptospira, a obligate spirochaeta aerobic bacteria. Leptospirosis continues to be a significant problem in areas with high populations as in SEA countries. In Indonesia, leptospirosis still acts as a dangerous disease that continues to be neglected and continues to be a health problem. While in Semarang Health Profile in 2015, Semarang City is still at the first rank of cases and death of leptospirosis. The general objective of this research was to analyze the pattern of the spread of leptospirosis disease based on physical environmental risk factors in Semarang City in 2014-2016. The design of this study was cross sectional with the type of observational study with total sampling technique. The number of samples is 134. Spatial analysis using 9.3 Arcgis software. The result of spatial analysis showed that the measurement of case-by-river distance buffer was 73 cases (54,5%) with radius 50 - 300 m. Based on the flood area, the incidence of Leptopsirosis in Semarang City in 2014 - 2016 was 26.11% (35 respondents). More respondents in this study had drain distances of ≥ 2 meters of 51.5% (69 respondents) .The leptospirosis cases were present in areas with 101 to 300 mm / month or medium rainfall, which was 76 cases (56.7%). While the distance of garbage disposal most of the respondents (91.8%) are at a distance less than 500 meters. The results of the nearest neighbor analysis ratio show the pattern of split distribution. Prevention advice may be used for hypochlorite powder to anticipate the presence of leptospira bacteria and use personal protective equipment.